(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2020)
Binuclear complex of Zn(II) with cyclohexyl acetoacetate was obtained and structurally characterized for the first time. According to structural data, the crystal system is triclinic, space group P-1; a = 7.6530(4), b = 12.2412(8), c = 12.9102(9) Å; α = 90.198(5), β = 101.071(5), γ = 96.937(5) deg. The molecular structure corresponds to the formula [Zn2(C10H15O3)4(C2H5OH)2]. The complex is located in a special position to the symmetry center of the unit cell. The coordination polyhedrons of the Zn atoms are the same distorted octahedrons formed by six oxygen atoms. Each formed by 4 oxygen atoms in the equatorial position, which belong to three ligand molecules: terminal ligand (2 oxygen atoms) and bridged ligand (1 oxygen atom) which chelate the zinc atom of the named polyhedron and 1 oxygen atom belong to a bridged ligand that chelates the other nucleus and monodentantly coordinated to mentioned one. Two oxygen atoms occupy an axial position, one of which belongs to the terminal ligand, mentioned above and the other to the coordinated ethanol molecule. The bond between the complex nuclei is stabilized by two hydrogen bonds formed by the hydrogen atoms from hydroxyl groups of ethanol molecules and the enol oxygen atoms of the terminal ligands of the other nucleus. The compound was also characterized by IR-spectroscopy, characteristic bands (сm-1) are: ν(C–H) - 2936, 2860, ν(C=O) & ν(C=C) – 1612, ν(C=O) + δ(C–H) – 1532, ν(C=C) & ν(C-CH3) – 1252, δ(C–H) – 1172, π(C–H) – 784, ν(M–O) – 456, 416. IR spectroscopy data confirm the bidentate coordination of cyclohexyl acetoacetate to zinc atoms in deprotonated form with the formation of chelated metallocycles. The structure of the complex is similar to the structures of cobalt and nickel complexes with cyclohexyl acetoacetate. Analysis of XRD-data (which are supplemented with this work) for Co(II), Ni(II) and Zn(II) complexes with acetoacetic acid esters shows that their structure, in particular the number of metal centers in the structures, regardless of the nature of the central atom or the alcohol fragment, but determined the presence of components capable of complementing the coordination sphere of the metal in reaction media.